The predictive validity of RETTS-HEV as an acuity triage tool in the emergency department of a Danish Regional Hospital. (February 2016) - Pérez, Noel; Nissen, Louise; Nielsen, Rasmus F.; Petersen, Poul; Biering, Karin
Abstract : Introduction: The Rapid Emergency Triage and Treatment System – Hospital Unit West (RETTS-HEV) is a triage system used in the emergency department (ED) in Herning, Denmark, since 2010. It categorizes patients according to priority and defines a time limit on how long patients can wait before being seen by a doctor depending on the severity of their condition. The purpose of this study was to determine the predictive validity of RETTS-HEV by measuring the association between triage scores and outcomes such as the admission rate, the length of stay (LOS), and mortality. Materials and methods: We performed an observational cohort study by examining the medical records of all patients who attended the ED from 1 September 2012 to 30 November 2012, at the Regional Hospital West Jutland in Herning, Denmark ( N =4680). We defined the following outcomes to make associations with the patients' triage category: in-hospital mortality, and 30, 60, and 90-day mortalities, the hospital LOS and the admission rate, on the basis of complete information from the Danish National Patient Registry. Results: The distribution of age, comorbidity, admission, LOS, and mortality over triage categories differed as expected. After making adjustments for these differences, we found a consistent association between triage categories and in-hospital mortality, and 30, 60, and 90-day mortalities, the hospital LOS, and the admission rate. Conclusion: RETTS-HEV was found to be closely related to all examined outcomes, and therefore useful in the risk stratification of ED patients.